Usnea Lichen community biomass estimationon volcanic mesas, James Ross Island, Antarctica - Bohuslavová, O.; Šmilauer, P.; Elster, J. (Josef) (Polar Biology, 2012)
Long - therm monitoring of lichen communities in respect to their reaction to ongoingclimatic changes in Antarctica. This study proves that macrolichens in maritime Antarctica can be monitored non-destructively by simple field methods combining digital photography and measurements of lichen thalli in botanical squares.